Pengaruh Capital Adequacy Ratio, Non Perfoming Loan, Loan To Deposit Ratio dan Biaya Operasional Pendapatan Operasional Terhadap Profitabilitas: Studi Empiris Pada Perusahaan Sub Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Agnes Fadilla Astriliana; Slamet Mudjija (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In 2019-2023, the average profitability in the banking sub-sector has increased and decreased. This study aims to analyse the Capital Adequacy Ratio, Non Performing Loan, Loan to Deposit Ratio and Operating Cost of Operating Income on Profitability. The research methodology used in this study uses quantitative methods. Data obtained from the Indonesia Stock Exchange website (www.idx.co.id) and www.bi.go.id. The population in this study are banking subsector companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling technique used purposive sampling technique with a sample of 22 (twentytwo) companies. Data analysis for hypothesis testing using Multiple Linear Regression with the help of the Statistical Package for Social Sciences (SPSS) version 22 (twenty-two) programme. The results showed that Capital Adequacy Ratio and Loan to Deposit Ratio had no effect on Profitability, while Non Performing Loan and Operating Cost of Operating Income had a negative effect on Profitability.